Natural fiber-reinforced mortars - Kesikidou, Fotini; Stefanidou, Maria (Journal of Building Engineering, 2019)
Using recycling materials in construction is a safe way for achieving sustainability. Although European policy, through directives given, supports their use and coherent research results derive from the scientific society, their use in practice is limited. It is generally accepted that the use of alternative construction materials with low environmental impact and of low cost is an important issue. As a part of the integration in sustainable development approach, the eco-friendly materials present a great interest in building construction manufacturing. Towards this direction, many studies have been focused on the exploitation of natural fibers as reinforcements in building materials. This study is an attempt to add more experimental results by the use of bio-fibers to building materials in order to ensure the performance of recycled materials such as bio-fibers in the construction sector. Three types of natural fibers jute, coconut and kelp were used as additives in 1.5% by mortar volume. Their role in cement and lime mortars was recorded by testing mechanical, physical and microstructure properties. The results indicate that natural fibers act in favor of strength and durability. Nevertheless, bio-fibers work differently in strong cement mortars in relation to the “soft” lime-based materials. Advantages can be gained in both cases but certain aspects should be taken into account such as the adhesion to the mortar matrix and the water content of the mixture. •Bio fibres are introduced in “soft” lime based mortars and in “strong” cement mortars.•Flexure and fracture energy were enhanced in both binding systems by the addition of bio fibres.•Lime mortars were benefited by the bio fibres in both mechanical and physical properties.•Cement mortars are benefited by rich in lignin fibers.